Sandwich ELISA for detecting urinary Survivin in bladder cancer - Li, Xuefeng; Wang, Yaming; Xu, Jianjun; Zhang, Qingyun (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
Objective: Survivin as a tumor marker in the diagnosis of bladder cancer has not been completely confirmed yet and there are few reports about using Survivin enzyme-linked immunosorbent assay (ELISA) kit to detect the urine of bladder cancer patients. This study aimed to develop a Survivin ELISA and validate its value in the detection of bladder cancer. Methods: Through square matrix titration, different combinations of coating antibody and detecting antibody, a Survivin ELISA was constructed. This assay was evaluated according to intra-assay precision, inter-assay precision and minimum detectable dose (MDD). Survivin levels were detected and analyzed in 102 bladder cancer patients and 102 healthy people by established ELISA. Then cutoff value was defined according to the analysis of receiver operating characteristic (ROC) curve. The sensitivity and specificity of detection were calculated on the basis of cutoff value to diagnose bladder cancer patients. Furthermore, the value of Survivin expression detected by ELISA among different clinicopathological characteristics of patients was also compared. Results: Through optimization of different conditions, intra-assay precision was 8.39%, inter-assay precision 8.57% and MDD 0.0625 ng/mL in this assay. When the optical density at 450 nm (OD450) was 0.09, it could get the optimized diagnostic cutoff value. According to this value, the sensitivity and specificity of diagnosis in bladder cancer patients were 70.6% and 89.2%, respectively. The associations between patients’ clinical variables and OD450 were not significant except tumor numbers in patients. Conclusions: This experiment has preliminarily developed a Survivin ELISA and confirmed Survivin as a biomarker which owned a practical and significant value in the diagnosis of bladder cancer.